Implementation of the Pentahelix Concept as Leader Policy in Developing UMKM - Fauzi Darsono, M. Gumilar; Saripa, Iip; Kamarubiani, Nike; Emi, Chiara (Universitas Negeri Padang, 2024)
The development of MSMEs in the Cibeureum Village in the collaboration era is very dependent on the implementation of the policies of the Cibeureum Village Head, South Cimahi District, and Cimahi City. Village side are encouraged to be able to develop various innovations in the development of MSMEs by paying attention to the five elements of collaboration that are incorporated in the penta helix. The five elements are government, academia, the private sector, the media, and society. This paper will explain the innovation model for MSME development as an effort to improve the welfare of the Cibeureum Village community using the penta helix concept. The method used is descriptive-qualitative. The research was conducted on MSME actors in Cibeureum Village. The result of this research is a new innovation in the form of a sustainable assistance model to optimize MSMEs in Cibeureum Village. This innovation is expected to have an impact on increasing economic welfare through MSMEs. Keywords: MSMEs, Policy, Penta helix